AN ANALYSIS OF ENGLISH SUMMATIVE TEST ITEMS OF TWELFTH GRADE STUDENT OF MAN 2 MERANGIN ACADEMIC YEAR 2019/2020 - Risnita; Zurnelli, Netti; Fitria, Wahyuni; Makrub (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2020)
The purpose of this research is to evaluate the validity, reliability, level of difficulty, discriminating power, and distractor efficacy of the English summative test items for the 12th grade MAN 2 Merangin students for the 2019-2020 academic year. This is a quantitative descriptive study. The subjects of this research were the questions from the 2019/2020 MAN 2 Merangin 12th grade English summative examination. Questions, answer keys, and student responses were included in the documentation used for the data collection technique. The quantitofive technique is used to analyze the validity, reliability, level of difficulty, discriminating power, and distractor efficacy of the dofa. The obtained dofa were analyzed using manual Microsoft Excel calculations. The results indicate that there are 38 valid items (76%) and 12 invalid items (14%); the questions on the English summative test of 12th grade students of MAN 2 Merangin for the 2019-2020 academic year are unreliable with a reliability level of 0.422; there are 12 items with an easy level of difficulty, 34 with a medium level of difficulty, and 4 with a difficult level of difficulty; and there are 22 poor items.